Kesiapsiagaan Masyarakat Terhadap Ancaman Bencana Tsunami di Kota Pariaman - ananda, Livia tri (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
This study aims to determine 1) the level of tsunami hazard in Pariaman City, 2) the level of community preparedness against the threat of a tsunami disaster in Pariaman City. The research method used in this research is descriptive quantitative research method. Based on the results of the study, the results obtained: 1) the level of tsunami vulnerability in Pariaman City is divided into 3 classes, namely high class 17.66%, medium class 71.64% and low class 10.70% of the area, 2) City community preparedness level Pariaman to tsunamis at high tsunami levels is in the very ready category at 79.5%, at the medium tsunami level in the ready category at 76.2%, and at low tsunami levels in the ready category at 70.1%.